The Internalization of Islamic Values in Pesantren - Andewi Suhartini (Jurnal Pendidikan Islam, 2016)
This article aims to describe the internalization of Islamic values in fostering akhlak (morality) of santri (Islamic boarding school students) in Pesantren (Islamic Boarding School) Miftahul Muhajirin Cidadap, Pagaden, Subang. The Internalization carried out in the forms of religious activities such as farḍu prayers in congregation, sunnah prayers Qiyãm al-lail and Ḍuha, sunnah fasting on Mondays and Thursdays, and recite Yasin after dawn. The Islamic internalization process of Islamic values takes several steps namely transformation values; transaction values; and trans-internalization values. The overview of akhlak santri from internalization results obtained from questionnaires data distributed to 53 santri. From the questionnaire data, it was obtained the categories of akhlak santri; excellent students (52.83%), good (45.28%), and quite good (1.89%).